Muslim Entrepreneurs with Disabilities in Digital Era: A Study of Islamic Management Practices and Social Empowerment - Muhajir Sulthonul Aziz; Moh Ilham (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – This trend of inclusive digital entrepreneurship among people with disability adhering to Islam represents a significant change in the way that marginalized communities are interacting with economic and religious spheres. The purpose is to examine how the presence of disabled Muslim entrepreneurs in social media is a space of managing Islamically business, empowerment and spiritual expressions. Design/methodology/approach – In this study a qualitative collective case study was carried out with five disabled Muslim entrepreneurs. Data were also collected by semi-structure interview, digital content observation and document followed by research method using code and category in analysing to interpret the managerial, spiritual, and empowerment in their practices of digital entrepreneurship. Findings – The paper concludes that social media is more than merely a marketing space, but is also an encompassing managerial space and spiritual space. Through the stories of the participants, they reveal how Islamic values of barakah, amanah and ihsan are interwoven into their business narrative. And they construct robust self-identities themselves and nurturing digital communities despite limitations in physicality and society. Research implications – The findings serve to demonstrate the power of social media to contribute towards more inclusive forms of Islamic entrepreneurship, particularly when experiences of lived spirituality are foregrounded. It also demonstrates the necessary option of policies for digital accessibility and faith-based business development among disabled people. Originality/value – The paper is amongst the first to provide a comprehensive analysis of Islamic management, disability inclusion and digital entrepreneurship through an empirically grounded synthesis at an analytical level. Keywords - Inclusive entrepreneurship, Islamic management, Disability, Social media. Paper type - Research paper